Case Report: Bone cement leakage in the right heart: a rare case of misinterpreted echocardiographic findings - Kong, Dongji; Xie, Xiaohong; Jin, Yong; Zhang, Yizhen (Frontiers in Surgery, 2025)
Bone cement leakage is a relatively common complication following percutaneous vertebroplasty (PVP); however, cement migration to the heart via the venous system is rare, causing severe chest pain and dyspnea. This case reports an 80-year-old male who presented to the Department of Infectious Diseases with mild fever, 2 months after undergoing PVP for a compression fracture of the third lumbar vertebra. A chest computed tomography initially misidentified the lesion as a pacemaker lead within the right ventricle. However, echocardiography revealed that the distal bone cement was embedded in the myocardium of the right ventricular apex, leading to the diagnosis of bone cement leakage. Thereafter, the patient underwent an open-chest procedure with direct cardiac visualization for cement removal in the cardiac surgery department.